ANALISIS CONSUMERS TRUST AND SATISFACTION TERHADAP INTENSITAS PENGGUNAAN PRODUK DANA SYARIAH - Sanjayawati, Hilda (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the influence of consumers' trust and consumers' satisfaction on the intensity of the use of Islamic fund products, both savings, deposits, and other Islamic financial planning products. The study used a quantitative approach with a sample of 250 Islamic bank customers. The analysis was carried out using Structural Equation Modeling (SEM). The results show that consumer trust has a significant effect on the satisfaction and intensity of using sharia fund products. Satisfaction also has a direct effect on the intensity of use. This research makes a theoretical contribution to the development of an Islamic consumer behavior model as well as a practical contribution for Islamic banks in increasing customer loyalty through increased trust and satisfaction.